Pengaruh Tingkat Return Sertifikat Bank Indonesia Syariah (SBIS) Terhadap Penempatan Pada SBIS dan ROA Bank Umum Syariah di Indonesia - Naroh Kawiryawan; Meri Indri Hapsari (Universitas Airlangga, 2015)
In order to fulfill the need of banking industry that grew rapidly, Bank Indonesia create several monetary instrument. One of them is Islamic Certificate of Bank Indonesia (SBIS). This research aims to investigate the effect of return rate of SBIS to investment in SBIS and also the profitability of sharia commercial banks in Indonesia. The research method used is path analysis with three kind of variables, which is SBIS’s return rate as exogenous variable, investment in SBIS as intervening endogenous variable, and the profitability as endogenousvariable.The result of this research shows that SBIS’s return rate effects significantly positive to the investment in SBIS, but effects unsignificantly negative to the probability of sharia commercial banks. Meanwhile investment in SBIS has non-significantly positive effect to the profitability of sharia commercial banks.